Introduction to Balanced Nutrition in Teaching for Elementary School Students - Erhan Dimas Nugraha; Asep Bayu Dani Nandiyanto (Universitas Pendidikan Indonesia, 2022)
The current condition in Indonesia, especially in children, is still experiencing a double burden of nutrition, namely lack of and excess nutrition. Many factors are involved in nutritional problems in Indonesia. One of the efforts that support the prevention of nutritional problems is through direct socialization to children by providing information about balanced nutrition so that it is expected to be able to educate from an early age, especially in choosing the types of food that are good for health and the introduction of body conditions related to nutritional disorders. The purpose of this study is that students in the Tugu Negeri Desa Cihideung. Parongpong District, West Bandung Regency, Indonesia. get additional education about balanced nutrition and at the same time the introduction of canker sores as an example of a disease that can be caused by a nutritional disorder. filling out a questionnaire that is applied to early childhood with an age range of 7-9 years using pre-test and post-test questionnaires. The result is that from a total of 20 students who filled out the questionnaire, as many as 62 students (67%) experienced an increase in the score on their post test results, and as many as 100% of grade 1 students experienced an increase, this shows that the implementation can be well absorbed by most students. A good counseling process requires several supporting factors including careful preparation and during implementation, interactive material delivery techniques are needed, as well as good team coordination. Continuous activities need to be carried out to monitor the application of the knowledge gained from the results of the counseling so that it is hoped that there will be an increase in the health quality of Indonesian children. The child's body is stronger against infection with other diseases.